A Crisis Call For New Preventive Medicine : Emerging Effects Of Lifestyle On Morbidity And Mortality. - Knight, Joseph A. (World Scientific, 2004)
Of the ten most common causes of death in industrialized countries, atleast two-thirds are lifestyle related (i.e. poor nutrition, physicalinactivity, overweight/obesity, cigarette smoking, alcohol/drug abuseand the environment, among others). The rapidly expanding elder population will put further demands onhealth care systems already burdened by the elderly and thepoor. However, increasing age need not be associated with expandinghealth care costs if people improve their lifestyles.